Should Unemployment Benefits be Related to Previous Earnings? - Burkhard Heer (Center for Economic Studies and ifo Institute (CESifo), 2002)
In most OECD countries, unemployment benefits are tied to individual previous labor earnings. We study the progressivity of this indexation with regard to its effects on employment, output, and welfare in a calibrated general equilibrium model with search unemployment. Employment varies endogenously on both the intensive margin and the extensive margins as agents choose their labor supply (if employed) or their search effort (if unemployed) in order to optimize life-time utility. Compared to the case of lump-sum unemployment compensation, a system of insurance payments that are related to past contributions results in higher output and welfare. The effects on employment are negligible as employed workers rather accumulate more savings than to supply additional work in order to insure against the loss of employment.
Keywords: 330; earnings-related unemployment benefits; search unemployment; computable general equilibrium; overlapping generations